Untersuchungen zur Herstellung geträgerter mono- und bimetallischer Nanopartikel mithilfe von überkritischem CO2 - Müller, Sabrina Alexandra (KIT Scientific Publishing, 2016)
Mono- and bimetallic nanoparticles were deposited onto different powdered supports by Supercritical Fluid Reactive Deposition (SFRD). Carbon dioxide was used as supercritical solvent and hydrogen as reduction agent. In order to optimize the production process unknown factors influencing the particle and product properties were extensively studied.